Susceptibility and Multidrug Resistance Patterns of Escherichia coli Isolated from Cloacal Swabs of Live Broiler Chickens in Bangladesh - Muha. Ajijur Rahman Al Azad; Md. Masudur Rahman; Ruhul Amin; Mst. Ismat Ara Begum; Reinhard Fries; Asmaul Husna; Ahmed S. Khairalla; A.T.M. Badruzzaman; Mohamed E. El Zowalaty; Kannika Na Lampang; Hossam M. Ashour; Hafez Mohamed Hafez (Pathogens, 2019)
Antimicrobial resistance is a major health problem, particularly in developing countries like Bangladesh, where there is a paucity of information on resistance patterns and prevalence of antimicrobial determinants. Therefore, the aims of this study were to investigate the prevalence of resistance, including multi-drug resistance (MDR), and the associated genetic determinants in Escherichia coli isolates from cloacal swabs of live broiler chickens in Bangladesh. Altogether, 400 cloacal swabs (200 from Rajshahi and 200 from Dhaka divisions) were randomly collected from individual chickens in 50 broiler farms. E. coli was isolated and identified using conventional bacteriological culture and biochemical methods. The isolates were further confirmed using genus-specific 16S rRNAtargeted polymerase chain reaction (PCR) primers. Antimicrobial susceptibilities and MDR of the isolates against nine different antimicrobial agents (ampicillin, erythromycin, tetracycline, gentamicin, ciprofloxacin, levofloxacin, trimethoprim-sulfamethoxazole, colistin sulphate, and streptomycin) were determined using the Kirby-Bauer disc diffusion method. Resistance determinants of E. coli to ampicillin (blaTEM), streptomycin (aadA1), erythromycin [ere(A)], trimethoprim (dfrA1), and tetracycline [tet(A), tet(B)] were screened using PCR. Our results showed that all swab samples were positive for E. coli. The isolates were uniformly resistant to ampicillin, tetracycline, streptomycin, ciprofloxacin, erythromycin, and trimethoprim-sulphamethoxazole. The isolates exhibited highest susceptibility to colistin sulphate (73.5%), followed by gentamicin (49%), and levofloxacin (17%). All isolates were resistant to three classes of antibiotics, 204 isolates (51%) were resistant to four classes, and 56 isolates (14%) were resistant to five. The highest prevalence of antimicrobial resistance gene was recorded for tetracycline (tet(A):95.25%; tet(B):95.25%) followed by ampicillin (blaTEM:91.25%), streptomycin (aadA1:88.25%), erythromycin (ere(A):84.75%), and trimethoprim (dfrA1:65.5%). In conclusion, surveillance for MDR bacteria in poultry is a critical piece of knowledge, which would be useful for optimizing empiric antimicrobial treatments and exploring alternative antimicrobial agents.